Multi-factor statistical analysis of influencing factors for elite sports development - Jiang, Y.; Li, J.; Hua, F.; Wang, J. (International Journal of Sports Science and Engineering, 2007)
Sports developing depends on many relevant factors, such as local economy, education, population, geography, climate, GDP, culture, etc. In this paper, the achievement of nations in main games (such as Olympic Games) is used as dependent variable to indicate local sports developing level. 22 possible factors regarding sports developing level are considered as independent variable. By the main games data and linear regression method, we can find the relationship between the sport developing and the factors, directing the sport developing further.